Epidemiological burden estimates for pathologies with a nonconstant risk: an application to HCV in Italy according to age, Metavir score, and genotype. Issue 42 (October 2016) - Mancusi, Rossella Letizia; Andreoni, Massimo; d'Angela, Daniela; Sarrecchia, Cesare; Spandonaro, Federico
Abstract : Abstract: Between western European countries, the hepatitis C virus (HCV) endemic is highest in Italy. The main objective of this paper is to estimate the endemic diffusion of hepatitis C at the national level and by geographical area, with an extrapolation at the regional level and by uniform cohorts of subjects (by sex and year of birth). The secondary objective is a stratification by gravity of the estimated statistical figures to provide an overview of possible targets of the new anti-HCV treatments. PubMed and the Cochrane Library were searched for relevant Italian populations studies regarding HCV prevalence. Random and fixed effect models were used for pooling data. To develop the epidemiological model, a meta-analysis of studies of Italian populations and the explicit consideration of the changes in the etiology of the disease in different cohorts (by year of birth) of population and the impact of effective treatments that have been introduced since the 1990s. A Markovian transition model, which is based on the distribution of HCV+ and HCV Ribonucleic Acid (RNA)+ subjects, provides a plausible assessment of the Italian situation. The Meta-analysis of Observational Studies in Epidemiology recommendations/statements were followed. In 2014, 1569, 215 HCV+ subjects (95% credible interval [CrI]: 1202, 630–2021, 261) were estimated in Italy, with a 2.58% prevalence (95% CrI: 1.98%–3.33%). A total of 828, 884 HCV RNA+ subjects (95% CrI: 615, 892–1081, 123), which is equal to a 1.36% prevalence (95% CrI: 1.01%–1.78%), is higher in southern Italy and the islands (1.9%) than in central–northern Italy (1.1%). The predominance of adult and elderly subjects, with an old or very old infection, inevitably entails a significant number of HCV RNA+ subjects in the advanced stages of the illness. According to our estimates, approximately 400, 000 subjects have cirrhosis, decompensated cirrhosis, and hepatocarcinoma, with a median age of 70 years. The model aims to support policymakers to define action plans by providing an estimate of both the emerged infected population and nonemerged infected population by age, gender, gravity, genotype, and geographical area. In the future, the model may contribute to simulation of the costs and outcome of different action strategies that can be adopted by health authorities. Abstract : Supplemental Digital Content is available in the text